Investigation of Eighth-Grade Students’ Understanding of the Slope of the Linear Function - Birgin, Osman (2012)
Abstract This study aimed to investigate eighth-grade students’ difficulties and misconceptions and their performance of translation between the different representation modes related to the slope of linear functions. The participants were 115 Turkish eighth-grade students in a city in the eastern part of the Black Sea region of Turkey. Data was collected with an instrument consisting of seven written questions and a semi-structured interview protocol conducted with six students. Students’ responses to questions were categorized and scored. Quantitative data was analyzed using the SPSS 17.0 statistical packet program with cross tables and one-way ANOVA. Qualitative data obtained from interviews was analyzed using descriptive analytical techniques. It was found that students’ performance in articulating the slope of the linear function using its algebraic representation form was higher than their performance in using transformation between graphical and algebraic representation forms. It was also determined that some of them had difficulties and misunderstood linear function equations, graphs, and slopes and could not comprehend the connection between slope and the x- and y-intercepts. Keywords: Mathematics Education. Eighth-grade Students. Linear Functions. Slope. Misunderstandings. Investigando a Compreensão de Alunos do Oitavo Ano sobre a Inclinação de Funções Lineares Resumo Este estudo tem como objetivo investigar as dificuldades de alunos quando tratando de diferentes modos de representar a inclinação de funções lineares. Os participantes foram 115 estudantes de oitava série de uma cidade situada na parte leste da região do Mar Negro, na Turquia. Os dados foram coletados por meio de questionários escritos e complementados com um protocolo de entrevista semi-estruturada realizada com seis alunos. Os dados quantitativos foram analisados estatisticamente e para os qualitativos optou-se por uma análise descritiva. Verificou-se que o desempenho dos alunos em articular a inclinação da função linear usando sua forma de representação algébrica foi maior do que o desempenho nas questões relativas à articulação entre as formas de representação gráfica e algébrica. Outras dificuldades foram detectadas, como as relativas ao conceito de função linear e gráfico de funções; e a falta de entendimento sobre a conexão entre a inclinação e os pontos de interseção com os eixos. Palavras-chave: Educação Matemática. Funções Lineares. Inclinação. Desempenho de Estudantes